The global effort to eradicate rinderpest - Roeder, Peter; Rich, Karl M. (International Food Policy Research Institute, 2009)
During the past 70 years, concerted efforts by the national veterinary services of affected countries from Senegal to China and Russia to South Africa—aided by international organizations—have brought the once-dreaded rinderpest virus to the point of extinction. In the near future, we can expect to see a global declaration of freedom from rinderpest, the first time this has been achieved for a livestock disease. The devastation wrought by rinderpest stimulated the founding of veterinary schools in many countries, and provided the basis for the development of the veterinary profession. The legacy of control programs in the past 20 years includes vaccine innovations and the development of new epidemiological and surveillance tools that are based on participatory techniques. Additionally, the benefits derived from eradication are many, ranging from increased confidence in livestock-based agriculture to increased food security, protected rural livelihoods, technically more proficient veterinary services, an opening of trade into lucrative markets in the Middle East, and the safeguarding of Africa’s wildlife heritage from a serious threat to its dwindling populations. As for the financial benefits of rinderpest eradication, describing them is constrained because of a general lack of studies on the subject, and the fact that programs covering multiple issues often did not clearly discern the rinderpest problem. This analysis attempts to present lessons learned from the experience gained in eradicating rinderpest, and explores the socioeconomic gains made as a result.